Factors affecting Firm Value with Capital Structure as Intervening Variable - Cathy Ismantara; Irwanto Handojo (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The objective of this research is to obtain the empirical evidence regarding the effect of dividend policy, firm size, profitability, liquidity, firm growth, managerial ownership, institutional ownership, board of directors, board of commissioners and cash holding towards firm value mediated by capital structure to the effect of dividend policy, firm size and profitability on firm value. The population in this research is non-financial firms listed in Indonesia Stock Exchange from the year of 2018 to 2020. Samples were obtained through purposive sampling method in which 189 data were taken as the sample. This research uses multiple regression method and path analysis to test the hypotheses. The results of this research indicated that profitability, firm growth, institutional ownership, board of directors and capital structure affect firm value, while dividend policy, firm size, liquidity, managerial ownership, board of commissioners and cash holding do not affect firm value. Meanwhile, firm size and profitability affect capital structure, while dividend policy does not affect capital structure. This research also indicated that capital structure mediates the effect of dividend policy and firm size on firm value but does not mediate the effect of profitability on firm value.